Gear, gimmicks, gizmo's and goggles - A look at swim gear - Goldsmith, W. (coachesinfo.com)
There are many and varied training and racing aids on the market designed to help you swim faster. They can make training more interesting by adding variety to workouts and can help you focus on improving aspects of your stroke in isolation. The types of gear which are available and training sets using swim gear are presented.